2014
DOI: 10.1186/1546-0096-12-54
|View full text |Cite
|
Sign up to set email alerts
|

Procedural pain and patient-reported side effects with weekly injections of subcutaneous Methotrexate in children with rheumatic disorders

Abstract: BackgroundDespite the widespread use of subcutaneous methotrexate in treating pediatric rheumatic disorders, the amount of pain associated with the injections has not been quantified. Our study aims 1) to quantify the amount of pain associated with subcutaneous injections of methotrexate, 2) to explore predictors of pain, 3) to determine the frequency of patient-reported clinical adverse effects of methotrexate, and 4) identify coping strategies of patients and caregivers.MethodsPatients aged 4–17 years with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
1
18
0
4
Order By: Relevance
“…Even when the disease-related symptoms were under control, JIA treatments made their child sick in other ways. This finding is consistent with previous studies that also reported children with JIA experienced difficulty and side effects with some medications such as Methotrexate (Bechard et al, 2014; Mulligan et al, 2013; Mulligan, Wedderburn, & Newman, 2015). Parents struggled with administering injectable medications due to the pain and discomfort it caused the child.…”
Section: Discussionsupporting
confidence: 93%
“…Even when the disease-related symptoms were under control, JIA treatments made their child sick in other ways. This finding is consistent with previous studies that also reported children with JIA experienced difficulty and side effects with some medications such as Methotrexate (Bechard et al, 2014; Mulligan et al, 2013; Mulligan, Wedderburn, & Newman, 2015). Parents struggled with administering injectable medications due to the pain and discomfort it caused the child.…”
Section: Discussionsupporting
confidence: 93%
“…Methotrexate intolerance may be particularly evident among children with JIA (49), and there seems to be a strong positive association between side effects of methotrexate and needle pain (50,51). This intolerance was not the main topic in this study, but ndings indicated that intolerance played an important role in children's experiences with needle injections.…”
Section: Building Con Dence In Everyday Lifementioning
confidence: 61%
“…A (17) Todos D (20) Participaram do estudo crianças em uso de injeções (SC) de metotrexato. Avaliada a dor por escalas de dores, os participantes e os responsáveis foram treinados para aplicação das escalas.…”
Section: Metodologia Resultados Principaisunclassified
“…Os resultados dos estudos incluídos demonstraram que a tecnologia da HDC é um procedimento alternativo para a administração de medicamentos de diversas classes e tipos de tratamentos, para outras patologias e situações não restritas à diabetes e alergia infantil. Resultados significativos para as crianças que participaram dos estudos desta revisão são relativos à rápida melhora hemodinâmica e sintomática, com menor desconforto e ausência de eventos adversos graves (17)(18)(19)(20)(21)(22) .…”
Section: Discussionunclassified
See 1 more Smart Citation